An exploratory qualitative analysis of student midwives views of teaching methods that could build their confidence to deliver perinatal bereavement care. (April 2016) - Martin, Caroline J. Hollins; Robb, Yvonne; Forrest, Eleanor
Summary: Background: Equipping student midwives with confidence to deliver bereavement care to childbearing women is a challenge for midwifery lecturers. Objective: To explore qualitative data provided by student midwives who evaluated the workbook Bereavement care for childbearing women and their families (Hollins Martin & Forrest, 2013) to explore their views of potential teaching strategies that could build their confidence to deliver real bereavement care. Method: An exploratory qualitative thematic analysis was used to provide, analyse and report themes identified within data collected in a prior study. Participants: Participants were student midwives (n = 179) in their second/third year of a midwifery degree program at 1 of 3 universities in the UK were included in the study. Data collection/analysis: Data to evaluate effectiveness of the bereavement workbook as a teaching method was collected using a survey instrument. It was the comments written under questions by participants that were analysed in the present study. Findings: Three themes emerged: (1) increasing classroom interaction, (2) the importance of reflecting on emotions, and (3) need for experience. Discussion: Although this study has addressed delivery of education that relates to midwives, the findings are cross transferable to other healthcare educators, practitioners, and students. Several solutions are proposed that could potentially build student confidence to deliver bereavement care: lecturers should (1) encourage group discussion in the classroom to help build student confidence to emotionally cope during real bereavement events; (2) ensure students gain exposure by encouraging qualified midwives to include them in real bereavement events early on in their training, and (3) develop packages of perinatal bereavement scenarios for simulation and rehearsal in the clinical skills laboratory. Post-implementation, it is recommended that these teaching strategies be evaluated. Highlights: Classroom teaching does not build student confidence to manage real bereavement situations. Group activities that explore students' thoughts and feelings builds confidence. Student midwives require clinical rehearsals prior to authentic bereavement events. Qualified midwives should include students in real bereavement events.